2011
DOI: 10.4056/sigs.1613929
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of Desulfobulbus propionicus type strain (1pr3T)

Abstract: Desulfobulbus propionicus Widdel 1981 is the type species of the genus Desulfobulbus, which belongs to the family Desulfobulbaceae. The species is of interest because of its great implication in the sulfur cycle in aquatic sediments, its large substrate spectrum and a broad versatility in using various fermentation pathways. The species was the first example of a pure culture known to disproportionate elemental sulfur to sulfate and sulfide. This is the first completed genome sequence of a member of the genus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 40 publications
(69 reference statements)
0
25
0
Order By: Relevance
“…Geobacter species were well known for the capacity to directly accept electrons from polarized electrode [19] and distributed sparsely on electrode surface in short rod-shaped [5,7]. The sequence of band A-6 was 100% similar to that of Desulfobulbus propionicus, which was ellipse-shaped bacteria [20] and could grow via electron transfer to electrodes [21]. The results from DGGE and the observation with SEM suggested that the corresponding bacterium were responsible for sulfate reduction using electrons from negatively poised electrode.…”
Section: Morphological and Molecular Characterization Of The Working mentioning
confidence: 77%
“…Geobacter species were well known for the capacity to directly accept electrons from polarized electrode [19] and distributed sparsely on electrode surface in short rod-shaped [5,7]. The sequence of band A-6 was 100% similar to that of Desulfobulbus propionicus, which was ellipse-shaped bacteria [20] and could grow via electron transfer to electrodes [21]. The results from DGGE and the observation with SEM suggested that the corresponding bacterium were responsible for sulfate reduction using electrons from negatively poised electrode.…”
Section: Morphological and Molecular Characterization Of The Working mentioning
confidence: 77%
“…For the type strain of Desulfobulbus propionicus DSM 2032, the genome is 3,881,859 bp long and contains 3,408 genes with 3,351 coding for protein and 57 RNA genes (Paganini et al 2011). The mol% G+C of the DNA is 58.93.…”
Section: Genome Comparisonmentioning
confidence: 99%
“…They are also capable of mixotrophic growth, i.e., simultaneous utilization of H 2 and organic substrates. As its name implies, Desulfobulbus propionicus is able to disproportionate elemental sulfur to sulfate and sulfide and is of great environmental and industrial interest not only due to its impact on the sulfur cycle in aquatic sediments but also its large substrate spectrum and a broad versatility in using various fermentation pathways (Pagani et al 2011). …”
Section: Dfi Genes Occur In Select Microorganisms Onlymentioning
confidence: 99%